Sport and school burnout in Norwegian lower secondary school student-athletes: A person-oriented approach - Saarinen, M.; Phipps, D. J.; Jordalen, G.; Bjørndal, C. T. (Journal of Clinical Sport Psychology, 2025)
The study examined burnout profiles in adolescent student-athletes based on sport and school burnout symptoms. We explored whether psychological distress, self-esteem, athletic identity, and student identity were associated with these profiles, accounting for age, gender, and type of sport. Participants included 642 student-athletes from Grades 8-10 (age 12-14, 57% males and 43% females) in eight Norwegian sport schools. Using latent profile analysis, we identified five profiles: mild sport and school burnout (46%), high burnout (22.5%), well-functioning (17.9%), predominantly school burnout (8.6%), and predominantly sport burnout (5%). Female student-athletes and those in Grades 9-10 were more at risk. Low self-esteem and high psychological distress increased the likelihood of burnout in sport and school, while a strong student identity seemed to protect against school burnout. These findings suggest that combining competitive sport with education at an early age may put student-athletes at risk for burnout symptoms in sport and school.